PENERAPAN TEORI BEHAVIORISTIK MELALUI PENDEKATAN APPLIED BEHAVIOR ANALYSIS (ABA) UNTUK MENINGKATKAN KEMAMPUAN ADAPTIF ANAK DENGAN ADHD - Pane, Mahfuzha; Fitria Sabila, Devi; Rizky Fauzy, Muhammad; Simaremare, Aman; Lubis, Zuraida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Applied Behavior Analysis (ABA) in improving the adaptive abilities of children with Attention Deficit Hyperactivity Disorder (ADHD). Children with ADHD generally experience difficulties in controlling behavior, paying attention, and adjusting to social and academic environments. The ABA approach, which is based on behavioristic principles such as reinforcement, shaping, and repetition, is used as a systematic intervention to shape the expected adaptive behavior. The research method used is a qualitative approach with a descriptive type to understand the application of behavioristic theory through the Applied Behavior Analysis (ABA) approach in improving the adaptive abilities of children with ADHD. The study was conducted at SD IT Nurhikmatika, Kolam Village, with one subject, as ADHD, and informants, the class teacher and parents who were selected purposively based on direct involvement in learning. Data collection techniques included observation, interviews, and documentation. The results showed that consistent application of ABA can improve children's adaptive abilities, such as compliance with instructions, social interaction skills, and independence in daily activities. Thus, the ABA approach is effective as a behavioristic theory-based intervention strategy to help children with ADHD develop their adaptive functions.